The Effectiveness of Discovery Learning-Based Biodiesel Production Practice in Improving Students’ Creative Thinking Skills on Renewable Energy Subject Matter - Faisal, Nur Zamzam Yuniar; Dadan Rosana; Insih Wilujeng; Laifa Rahmawati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This study aims to determine the effectiveness of biodiesel production practice in enhancing the creative thinking skills of eighth-grade students at junior high school in Sleman in the renewable energy topic. The research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 25 students selected purposively from one class. The instrument used was a creative thinking skills test covering indicators of flexibility, fluency, originality, elaboration, and sensitivity to problems. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, n-Gain calculation, and effect size measurement. The results showed an improvement in students’ creative thinking skills with a medium category n-Gain and a very large effect size (1.84), along with a significant difference between pretest and posttest scores (p < 0.05). The biodiesel production practice proved effective in developing students’ creativity. This study provides important implications for developing practical-based learning methods that are relevant to environmental and renewable energy issues.